Recent Trends in Financial Technology (FinTech): Disruption, Innovation, and Policy Implications - Amardeep Bajpai, (AG Volumes, 2025)
Financial technologies (FinTech) are becoming a widely accepted force of transformation in economic systems that change the manner in which policies are developed, executed, and assessed. Driven by disruptive technologies like "blockchain and artificial intelligence", which have transformed big data analysis, the fintech sector has radically changed the financial environment. This review examines recent trends in Financial Technology (FinTech), focusing on innovation, disruption in banking, and policy implications. It emphasizes how technology like blockchain, artificial intelligence, and big data can improve productivity and financial inclusion. The study emphasizes the importance of government support, digital literacy, and adaptive regulation to balance innovation, security, and sustainability in the evolving FinTech ecosystem.